Isolation and Identification of Lactic Acid Bacteria from Buffalo’s Raw Milk in Basrah Province by Sequencing the 16S rRNA. (Indian Journal of Forensic Medicine & Toxicology, 2020)
Milk is a nutrient substance that screted from mammary glands of mammals. Lactic acid bacteria (LAB)of raw milk are natural microflora and might be starter cultures for milk fermentation. This study aimed toisolate LABs from raw buffalo’s milk and identify them by 16S rRNA sequencing for possible uses in themanufacture of food product., A total of 30 buffalo’s raw milk samples were collected from different areasof Basrah province (Shut-Alarab,Al-Zubair,Al-Qurna, Basrah conter and Abi-Elkhasib through the periodextended from October to December 2019 to isolate the LABs using conventional bacteriology test andidentify them by 16S rRNA sequencing using Polymerase Chain Reaction assay (DNA-based method).DNA extraction was carried out in duplicate for all raw milk samples. The results showed buffalo’s milkraw showed positive result for bacteriological test (Gram positive-catalase negative)and for the presenceof the 16S rRNA gene. There was no significant difference among ages, months, and area of the currentstudy. Buffalo’s raw milk at >4-8 year of age showed a higher ratio of LABs (71.43%) compared with thatof buffalo at >1-4 year of age (47.83%). In addition, the highest ratio of LABs in buffalo’s raw milk was inOctober (66.6%) and the lowest one was in November (36.3%). Furthermore, the highest ratio of LABs inbuffalo’s raw milk was in Abi- Elkhasib (100 %) and the lowest one was in AL-Zubair (20%). In conclusionLactic acid bacteria were found in buffalo’s raw milk. Biochemical and genotypic tests are effectively usedto identify the LABs. All LABs isolates could be survived well in buffalo’s raw milk in any age per year,months, and area of study. These findings suggest the possibility that LABs isolates from buffalo’s raw milkmight use to inhibit pathogenic and spoilage bacteria in the food products and might improve flavour andquality of the food products.